Comparison of plaque distribution and wire-free functional assessment in patients with stable angina and non-ST elevation myocardial infarction: an optical coherence tomography and quantitative flow ratio study. Issue 2 (19th August 2020) - Dan, Kazuhiro; Garcia-Garcia, Hector M.; Yacob, Omar; Kuku, Kayode O.; Kolm, Paul; Shah, Nikunj; Bennett, Martin R.; Curzen, Nick; Waksman, Ron; Mahmoudi, Michael
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: Data comparing plaque characteristics and wire-free physiological assessment in the target vessel in patients with stable angina versus acute coronary syndrome are sparse. Therefore, we investigated the difference in plaque distribution between stable angina and non-ST-elevation myocardial infarction (NSTEMI) and explored the relationship between target vessel vulnerability by optical coherence tomography (OCT) and wire-free functional assessment with quantitative flow ratio (QFR). Methods: Patients with stable angina ( n  = 25) and NSTEMI ( n  = 24) were in the final prospective study cohort from the DECODE study (ClinicalTrials.gov, NCT02335086). All 5480 OCT frames in the region of interest were analyzed to study plaque morphology in the target vessel. QFR was analyzed from baseline coronary angiography before percutaneous coronary intervention. Vulnerable vessel score (VVS) was calculated from each plaque, and vessel QFR was then compared. Results: Out of all frames, thin-cap fibroatheroma was common with NSTEMI compared to stable angina (10.9 versus 6.3%, P  < 0.01), while fibrous plaque was more commonly seen with stable angina compared to NSTEMI (19.7 versus 14.4%, P  < 0.01). Calcified plaque was similar in both clinical settings (approximately 6%). Regression analysis showed that segments with normal vessel walls were located significantly farther from the other plaque types. Longitudinal distances for plaque-type in NSTEMI were numerically greater than those for stable angina; however, the mean difference was less than 10 mm. The VVS had a significant inverse linear correlation with QFR ( r  = −0.34, P  = 0.009). Conclusions: The plaque distribution by OCT between stable angina and NSTEMI was similar. Target vessel vulnerability was greater in patients with lower QFR value.